2017
DOI: 10.1155/2017/7897614
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the FSI Characteristics in a Tubular Pump

Abstract: Flow condition was simulated in a shaft tubular pump by using the Shear-Stress Transport (SST) k-ω turbulence model with high quality structured grids in design condition. Corresponding structural vibration characteristics were then analyzed based on two-way coupled Fluid-Structure Interaction (FSI) method. Fluid results showed that flow in the outlet flow passage was a combination of the axial flow and circumferential rotation motion. Time and frequency domain analysis of pressure pulsation of typical measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, several studies focused on improving and optimizing the pump performance for different pumps such as reactor coolant pumps, multiphase pumps, centrifugal pumps and pulp pumps, by using the orthogonal optimization method. [22][23][24][25] However, there were many researches [26][27][28] in addition to the above researches about tubular pumps, previous studies focused mainly on traditional tubular pumps with an operating head less than 5 m, and only a few studies regarding the performance of tubular pumps with an operating head more than 5 m have been reported. With the extensive construction of long-distance water transfer projects, new challenging requirements for tubular pumps are being proposed, such as high operating head, high efficiency and low shaft power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies focused on improving and optimizing the pump performance for different pumps such as reactor coolant pumps, multiphase pumps, centrifugal pumps and pulp pumps, by using the orthogonal optimization method. [22][23][24][25] However, there were many researches [26][27][28] in addition to the above researches about tubular pumps, previous studies focused mainly on traditional tubular pumps with an operating head less than 5 m, and only a few studies regarding the performance of tubular pumps with an operating head more than 5 m have been reported. With the extensive construction of long-distance water transfer projects, new challenging requirements for tubular pumps are being proposed, such as high operating head, high efficiency and low shaft power.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were many researches 2628 in addition to the above researches about tubular pumps, previous studies focused mainly on traditional tubular pumps with an operating head less than 5 m, and only a few studies regarding the performance of tubular pumps with an operating head more than 5 m have been reported. With the extensive construction of long-distance water transfer projects, new challenging requirements for tubular pumps are being proposed, such as high operating head, high efficiency and low shaft power.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 22 analyzed the pressure pulsation in a centrifugal pump by SST k-ω model, which has accurate results. Wang et al 23 analyzed the pressure pulsation in a tubular pump by SST k-ω model. Therefore, CFD has become a mature technology for analyzing pressure pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…Negru and Muntean 24 used a one-way fluid-structure interaction method to obtain the stress distribution of the pressure and suction surfaces of a Francis runner blade. Wang et al 25 used a tubular turbine as an example to analyze the stress concentration at the connection between the leading edge of the blade and hub. Müller et al 26 used fluid dynamics and finite element analysis to evaluate hydraulic pump-turbines and showed that the external excitation frequency is much lower than the modal vibration frequency of the runner, which does not cause resonance.…”
Section: Introductionmentioning
confidence: 99%